Influence of aggregate temperature before mixing of BSM-emulsion and BSM-foamed on compaction density, tensile strength, and shear properties - Ts'ese, Iketsetseng (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.